1989
DOI: 10.1159/000195796
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar Lavage Analysis with Anti-T6 Monoclonal Antibody in the Evaluation of Diffuse Lung Diseases

Abstract: To evaluate the usefulness of anti-T6 monoclonal antibody cell analysis in the assessment of diffuse lung disease, 77 bronchoalveolar lavages (BAL) were performed on 70 subjects: 18 normal smokers, 14 normal nonsmokers, 30 patients with chronic interstitial lung diseases (15 sarcoidosis, 12 idiopathic or associated pulmonary fibrosis, 3 histiocytosis X) and 8 patients with diffuse lung neoplastic disorders. The percentage of T6-positive cells was significantly higher in normal smokers than in normal nonsmokers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 8 publications
1
8
1
1
Order By: Relevance
“…Although Auerswald et al 16 and Chollet et al 19 reported good sensitivity of immunocytochemistry against CD1a in BAL fluid as a diagnostic test 16,19,20 , our data are more in accordance with recent evidence indicating a low sensitivity of this approach 21 . Examination of the BAL fluid may be of value in patients with atypical clinical and/or radiological presentation when it can be used to exclude other interstitial lung diseases with more typical lavage findings (e.g., sarcoidosis) and pulmonary infections, such as cavitary forms of Pneumocystis Jiroveci pneumonia or mycobacterial infections.…”
Section: Discussionsupporting
confidence: 90%
“…Although Auerswald et al 16 and Chollet et al 19 reported good sensitivity of immunocytochemistry against CD1a in BAL fluid as a diagnostic test 16,19,20 , our data are more in accordance with recent evidence indicating a low sensitivity of this approach 21 . Examination of the BAL fluid may be of value in patients with atypical clinical and/or radiological presentation when it can be used to exclude other interstitial lung diseases with more typical lavage findings (e.g., sarcoidosis) and pulmonary infections, such as cavitary forms of Pneumocystis Jiroveci pneumonia or mycobacterial infections.…”
Section: Discussionsupporting
confidence: 90%
“…Secondly, increased numbers of Langerhans' cells are recovered from cigarette smokers and patients with other diseases that lead to alveolar epithelial hyperplasia (including fibrotic interstitial lung diseases) and, in our experience, the number of Langerhans' cells observed in such patients overlaps to a large extent with the number recovered from patients with pulmonary LCH 636 37 Thus, in contrast to some reports,38 39 especially those evaluating infants and children,40 we found that, if the threshold for a positive result is fixed at 5% Langerhans' cells, the test is specific but the sensitivity is quite low (<25%).…”
Section: Fibreoptic Bronchoscopy and Bronchoalveolar Lavagecontrasting
confidence: 53%
“…The identification of LCs among cells recovered by lavage using monoclonal antibodies directed against CD1a (OKT6 or equivalent) has previously been suggested to be useful as a diagnostic test in PLCH [36][37][38], but more recent evidence indicates that this approach can be disappointing and lacks sensitivity. False positive results are common and the specimens must be examined by an experienced cytologist.…”
Section: Pulmonary Langerhans' Cell Histiocytosismentioning
confidence: 99%